تحليل صدق بنود أسئلة الاختبار النهائي الوطني الموحد للمدارس المتوسطة الإسلامية لمادة اللغة العربية و صعوبة بنودها و تمييزها ببريجين باسوروان - Anik Yuliana (Universitas Yudharta Pasuruan, 2017)
Nahwu is very Important to Understand the Arabic text. However, most learning Nahwu less applicable especially for beginners. The application of ”Inquiry-Discovery” learning method, the Nahwu at Students Halaqah Wustho Ngalah Islamic Boarding School. This study purposes to know the significance of differences students understanding level on the Nahwu before and after the ushing the “Inquiry-Discovery” learning method at grade Nahwu at Students Halaqah Wustho Ngalah Islamic Boarding School. Being the method used for data collection in this study is Testing, Observation, interview,test and using the formula T-test while the Test formula by using SPSS.16 applied to determine whether there is influence of the using “Inquiry-Discovery” learning method to improve understanding Nahwu. The result showed there are the effectiveness of using “Inquiry-Discovery” learning method to improve the eleventh graders understanding on the Nahwu at Students Halaqah Wustho Ngalah Islamic Boarding School it can be seen from the test T over T-table values (4,683> 2,120) wich means are Ho refused and Ha accepted.